2014
DOI: 10.1111/pce.12313
|View full text |Cite
|
Sign up to set email alerts
|

Relax and refill: xylem rehydration prior to hydraulic measurements favours embolism repair in stems and generates artificially low PLC values

Abstract: Diurnal changes in percentage loss of hydraulic conductivity (PLC), with recorded values being higher at midday than on the following morning, have been interpreted as evidence for the occurrence of cycles of xylem conduits' embolism and repair. Recent reports have suggested that diurnal PLC changes might arise as a consequence of an experimental artefact, that is, air entry into xylem conduits upon cutting stems, even if under water, while under substantial tension generated by transpiration. Rehydration proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(128 citation statements)
references
References 68 publications
6
117
3
2
Order By: Relevance
“…However, recent publications have provided evidence that some measurement techniques used to evaluate the hydraulic function and vulnerability to cavitation of plant organs may be prone to artifacts (Sperry et al, 2012;Torres-Ruiz et al, 2014;Trifilò et al, 2014). The discovery of these artifacts has raised questions regarding the reliability of some previously published plant hydraulics data, in particular data relating to the refilling of embolized xylem conduits while the xylem is under tension.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, recent publications have provided evidence that some measurement techniques used to evaluate the hydraulic function and vulnerability to cavitation of plant organs may be prone to artifacts (Sperry et al, 2012;Torres-Ruiz et al, 2014;Trifilò et al, 2014). The discovery of these artifacts has raised questions regarding the reliability of some previously published plant hydraulics data, in particular data relating to the refilling of embolized xylem conduits while the xylem is under tension.…”
mentioning
confidence: 94%
“…Whereas Scoffoni and Sack (2014) showed that the artifact described by Wheeler et al (2013) has no impact on leaf xylem hydraulic conductance, there is some uncertainty about its importance in stems or shoots (Trifilò et al, 2014;Venturas et al, 2014). The results of Wheeler et al (2013) indicate that more embolism could be induced by cutting samples that are under midrange xylem tension (e.g.…”
mentioning
confidence: 94%
“…(2) To avoid artefactual embolism induction caused by the cutting of a branch, while the xylem is under tension, rehydration/relaxation of samples has been suggested, followed by re-cutting under degassed water (Wheeler et al 2013), although this artefact has not been found by others (Venturas et al 2015). Alternatively, the relaxation procedure has been shown to introduce other potential errors related to rehydration-induced embolism refilling (Trifilo`et al 2014b). Recommendations for standardizing measurements of vulnerability curves have recently been described (Torres-Ruiz et al 2014).…”
Section: Methodological Precautionsmentioning
confidence: 99%
“…Future research should carefully evaluate the occurrence and magnitude of cutting or relaxation artefact in species investigated for their refilling capability. Trifilo`et al (2014b) suggested the use of refilling inhibitors (e.g. orthovanadate) to investigate the impact of cutting and relaxation on PLC values.…”
Section: Methodological Precautionsmentioning
confidence: 99%
“…In the laboratory, branches were repeatedly cut from both sites alternatively under water. In an earlier study (Beikircher and Mayr 2015), this harvesting and sampling protocol proved to be appropriate for preserving the hydraulic state and avoid artefactual embolisation as well as refilling (Trifilò et al 2014). Before June, shoots developed in the previous season were used for measurements, whereas from June onward, we used the respective current-year shoots.…”
Section: Sampling and Preparation Of Branchesmentioning
confidence: 99%